A Direct Arylation‐Cyclisation Reaction for the Construction of Medium‐Sized Rings. Issue 52 (7th September 2017) - Whitaker, Daniel; Batuecas, María; Ricci, Paolo; Larrosa, Igor
Abstract: A strategy for assembling biaryls linked through a medium‐sized ring is herein presented. π‐Complexation of fluoroarenes to chromium tricarbonyl activates the molecule towards both C−H activation and nucleophilic aromatic substitution without covalently altering the molecular connectivity of the arene. The construction of bridged biaryl molecules with 6–10‐membered core rings is achieved through a one‐pot C−H arylation/nucleophilic aromatic substitution sequence. The methodology is applicable to the synthesis of heterocyclic as well as fully carbocyclic rings. Abstract : One‐pot, two‐step, three rings : An intermolecular cyclisation reaction has been developed, combining direct C−H arylation with nucleophilic aromatic substitution. π‐Complexation of fluoroarenes to Cr(CO)3 greatly enhances the reactivity of both steps. Rings with 6 to 10 members are accessible through cyclisation with O, N and C‐centered nucleophiles.